The Effect of Flap Design on Wound Healing after Periapical Surgery: A Comparative Study. - Mohammad S. Suleiman (University of Mosul, College of Dentistry, 2008)
Aims: To assess the clinical effect of different flap design that used in periapical surgery and theirrelation to untoward postoperative sequel. Materials and methods: Forty five patients were includedin the present study, they were divided randomly into three groups, each comprised of (15) patients. Inthe first group, apicectomy was done using intrasulcular triangular (2-sided) flap. Whereas, in thesecond group, a submarginal (Luebke-Ochsenbein) scalloped 2-sided flap was used. While in the thirdgroup, a new experimental (straight mucogingival) 2-sided flap was tested. Postoperative healing wasevaluated clinically in regard to oedema, alteration of soft tissue colour, recession of marginal gingiva,extent of scarring, and closure of the wound site. Assessment was done at 2, 7, 15 and 30 dayspostoperative intervals. Results: Comparison among the three study groups was performed. Statisticalanalysis revealed significant differences in the results of experimental flap over the other two types inregard to oedema, colour and wound closure with the superiority of the former on the latter flaps. Bothexperimental and Luebke-Ochsenbein flaps showed significant differences from intrasulcular incisionin their effect on gingival recession. In contrast, scarring was less evident in intrasulcular flap followedby experimental flap while in Luebke-Ochsenbein incision, this complication was significant.Conclusion: This study; however, revealed that the experimental flap allows for rapid and recessionfree healing following periapical surgery. In addition, inflammatory changes persist for longer time inthe intrasulcular and submarginal (Luebke-Ochsenbein) incision than in experemintal incision. So itwas concluded that the new flap design could provide an alternative.